WEE1 inhibition enhances the antitumor immune response to PD-L1 blockade by the concomitant activation of STING and STAT1 pathways in SCLC - Hirokazu Taniguchi; Rebecca Caeser; Shweta S. Chavan; Yingqian A. Zhan; Andrew Chow; Parvathy Manoj; Fathema Uddin; Hidenori Kitai; Rui Qu; Omar Hayatt; Nisargbhai S. Shah; Álvaro Quintanal Villalonga; et al. (Cell Reports, 2022)
Summary: Small cell lung cancers (SCLCs) have high mutational burden but are relatively unresponsive to immune checkpoint blockade (ICB). Using SCLC models, we demonstrate that inhibition of WEE1, a G2/M checkpoint regulator induced by DNA damage, activates the STING-TBK1-IRF3 pathway, which increases type I interferons (IFN-α and IFN-β) and pro-inflammatory chemokines (CXCL10 and CCL5), facilitating an immune response via CD8+ cytotoxic T cell infiltration. We further show that WEE1 inhibition concomitantly activates the STAT1 pathway, increasing IFN-γ and PD-L1 expression. Consistent with these findings, combined WEE1 inhibition (AZD1775) and PD-L1 blockade causes remarkable tumor regression, activation of type I and II interferon pathways, and infiltration of cytotoxic T cells in multiple immunocompetent SCLC genetically engineered mouse models, including an aggressive model with stabilized MYC. Our study demonstrates cell-autonomous and immune-stimulating activity of WEE1 inhibition in SCLC models. Combined inhibition of WEE1 plus PD-L1 blockade represents a promising immunotherapeutic approach in SCLC.